The association of Leptospermum honey with cytokine expression in the sinonasal epithelium of chronic rhinosinusitis patients - Jamil Manji (KeAi Communications Co., Ltd., 2019)
Objective: To identify the differences in cytokine expression between sinonasal tissue from patients treated with Leptospermum (Manuka) honey (LH) irrigation versus normal saline irrigation twice-daily for twelve weeks following sinus surgery (FESS). Methods: Forty-six CRS patients were recruited. Sinus tissue biopsies were collected during FESS and then at 5 and 12 weeks postoperatively during the course of treatment. A multi-plex cytokine assay quantified the abundance of 17 cytokines in biopsied tissue. Cytokine expression fold-change was analyzed between each time point using a robust linear regression model and compared between the two treatment groups. Results: Compared to the saline irrigation group, five cytokines were differently expressed (CI = 95%) in sinonasal tissue obtained from subjects in the LH irrigation group during the 12-week treatment period. Cytokines IL-6 (P = 0.0400), IL-8 (P = 0.0398), MCP-1 (P = 0.0284), and MIP-1β (P = 0.016) were significantly increased in the LH irrigation group compared to the saline irrigation group. IL-13 was significantly increased in the saline irrigation group compared to the LH group (P = 0.0086). Conclusion: LH may potentially act to modulate the expression of IL-6, IL-8, IL-13, MCP-1 and MIP-1β in sinonasal tissue. Keywords: Leptospermum honey, Sinusitis, Inflammation, Postoperative care, Irrigation